Consistency and Transformation of Filial Responsibility Attitudes in China: Evidence from Panel Study of Family Dynamics of 2004 and 2017. (February 2023) - Wang, Yongjie; Wan, Guowei; Gu, Yao
Objective: This study analyzes the trend of change and influencing factors of filial responsibility attitudes in China. Method: The study uses data of Panel Study of Family Dynamics (PSFD) conducted in three Southeast regions in China in the year 2004 and 2017. Results: This study has two major findings. First, there was no significant decline in filial responsibility attitudes over the decade in spite of aging tendency. Both Reciprocal Filial Piety (RFP) and Authoritative Filial Piety (AFP) have not declined, with similar trend to men and women. Second, factors affecting filial responsibility attitudes have changed over the 13 years, with the impact of educational attainment and employment declining, while the effect of marital status increasing. Gender heterogeneity in the process was obvious. Conclusion: This study adds to literature on filial piety in Confucian society and provides empirical evidence on the future of cross-cultural filial responsibility attitudes.